STUDY OF EATING BEHAVIOR AND LEVELS OF ANXIETY-DEPRESSIVE DISORDERS IN OBESE PATIENTS WHO HAVE NOT UNDERGONE BARIATRIC SURGERY - Kuchkarov Humoyun Nurali o’g’li (Modern American Journals, 2025)
Eating behavior is not only driven by physiological needs but is also closely intertwined with an individual's emotional and psychological state. Emotional, external, and restrained eating styles may be differently associated with mental health conditions, particularly anxiety and depression. Emotional eating, in particular, often develops as a coping mechanism to alleviate stress and psychological distress, and is frequently accompanied by symptoms of anxiety and depression. In recent years, there has been a growing number of studies aimed at identifying the relationship between eating behavior and affective disorders. As part of this research trend, the present study assessed levels of anxiety and depression in individuals with different eating behavior patterns using the Hospital Anxiety and Depression Scale (HADS), and statistical analysis was conducted to explore the differences between these groups.
Keywords: Bariatric surgery, depression, anxiety, eating disorder